At death’s door perceptions and translations of Filipino culture reflected in funeral home interior design - Patarata, ian Merrel G. (University of the Philippines Diliman, 2023)
This study aimed to investigate selected Filipinos' overall perceptions on the translation of culture reflected in Filipino funeral home interior design. The study utilized a qualitative research design, specifically a case study, and was analyzed through a thematic approach. Respondents were selected through purposive sampling and the funeral home was selected through convenience sampling. Twenty (20) respondents were asked to answer a survey questionnaire. Four participants from the pool of respondents were selected afterward to take part in an in-depth interview. Results indicated that the spatial and design elements present in funeral homes are seating furniture, surface furniture, and equipment that is frequently found in the Viewing Area, Private Room, Socialization Area, Kitchen, Common Restroom, and Food Preparation Area. The study shows that the St. Peter Chapels - Valenzuela is generally sufficient for common activities based on space requirements. Results also identified different reflections of culture in interior design. Values, such as hospitality, was reflected through the provision of sufficient seating furniture. Superstitions, such as avoiding sweeping the floors during a wake, manifested through the selection of flooring materials that are easy to maintain. The study interpreted that the level of awareness of these cultural reflections and beliefs is correlated to the level of attachment to the departed and their length of visit. It also revealed that respondents had mixed sentiments regarding the significance of reflecting culture in interior design, which could be attributed to a lack of knowledge or stimulation for observation in funeral home designs. The study concluded that the significance of cultural translation heavily relies on the personal insights of a person. The findings in this study can help funeral home establishments and builders in providing more culturally-relevant and culturally-sensitive funeral homes for Filipinos. The study also offers the opportunity to expand to specialization in burial and funeral spaces in the interior design discipline.